The Effect of Systemic Steroid on Hearing Preservation After Cochlear Implantation via Round Window Approach: A Guinea Pig Model. Issue 7 (August 2017) - Chang, Mun Young; Rah, Yoon Chan; Choi, Jun Jae; Woo, Shin Wook; Hwang, Yu-Jung; Eastwood, Hayden; O'Leary, Stephen J.; Lee, Jun Ho
Abstract : Hypothesis: When administered perioperatively, systemic dexamethasone will reduce the hearing loss associated with cochlear implantation (CI) performed via the round window approach. Background: The benefits of electroacoustic stimulation have led to interest in pharmacological interventions to preserve hearing after CI. Methods: Thirty guinea pigs were randomly divided into three experimental groups: a control group; a 3-day infusion group; and a 7-day infusion group. Dexamethasone was delivered via a mini-osmotic pump for either 3 or 7 days after CI via the round window. Pure tone-evoked auditory brainstem response (ABR) thresholds were monitored for a period of 12 weeks after CI. The cochleae were then collected for histology. Results: At 4 and 12 weeks after CI, ABR threshold shifts were significantly reduced in both 7-day and 3-day infusion groups compared with the control group. Furthermore, the 7-day infusion group has significantly reduced ABR threshold shifts compared with the 3-day infusion group. The total tissue response, including fibrosis and ossification, was significantly reduced in the 7-day infusion group compared with the control group. On multiple regression the extent of fibrosis predicted hearing loss across most frequencies, while hair cell counts predicted ABR thresholds at 32 kHz. Conclusion: Hearing protection after systemic administration of steroids is more effective when continued for at least a week after CI. Similarly, this treatment approach was more effective in reducing the fibrosis that encapsulates the CI electrode. Reduced fibrosis seemed to be the most likely explanation for the hearing protection. Abstract : Supplemental Digital Content is available in the text